The Politics of authoritarian rule - Svolik, Milan W. (New York Cambridge University Press, 2012)
What drives politics in dictatorships? Milan W. Svolik argues that all authoritarian regimes must resolve two fundamental conflicts. First, dictators face threats from the masses over which they rule - this is the problem of authoritarian control. A second, separate challenge arises from the elites with whom dictators rule - this is the problem of authoritarian power-sharing. Crucially, whether and how dictators resolve these two problems is shaped by the dismal environment in which authoritarian politics takes place: in a dictatorship, no independent authority has the power to enforce agreements among key actors and violence is the ultimate arbiter of conflict.